Global distribution, genesis, and enrichment characteristics of high-concentration natural hydrogen - Yufei Liang; Qingqiang Meng; Xiaowei Huang; Wang Lu; Yongbo Wei; Jiayi Liu; Yuan Zhou; Lei Huang; Qi Li; Jiahui Chen; Dongsheng Zhou (Frontiers in Marine Science, 2025)
Under the global decarbonization initiative, natural hydrogen has garnered significant attention as a green, high-calorific-value, zero-carbon emission clean energy source in marine and continental contexts. Previous research on natural hydrogen systems remains nascent. This study systematically synthesized the distribution characteristics, genetic mechanisms, and enrichment processes of high-concentration natural hydrogen globally, yielding four key insights: (1) Natural hydrogen originates from complex processes broadly categorized as organic and inorganic, predominantly including deep-Earth degassing, water-rock reactions, and radiolysis of water. (2) Hydrogen-rich accumulations exhibit widespread distribution, primarily occurring in rift systems, plate collision zones, subduction zones and their peripheries, as well as Precambrian iron-rich formations. (3) Natural hydrogen reservoirs form through dynamic accumulation processes requiring: high-quality source supply, favorable migration pathways and preservation conditions, and sustained influx exceeding leakage rates. (4) Favorable exploration targets should avoid microbial active zones and deep hydrogenation/hydrocarbon generation regions; current evidence suggests promising reservoirs occur in ultra-deep settings, peripheral areas of convergent zones, and shallow strata proximal to deep-seated faults. Exploration of natural hydrogen should prioritize evaluating the hydrogen anomalies to identify potential reservoirs and advance systematic comprehension of this emerging energy play.